Work Effectiveness of Night Auditor in Front Office Department - Pande Putu Dion Narakusuma; I Nyoman Winia; I Gusti Putu Sutarma; I Putu Budiarta; I Dewa Gede Ari Pemayun; Ni Putu Somawati (International Journal of Travel, Hospitality and Events, 2022)
ABSTRACT Purpose: The purpose of this research is to analyze the work effectiveness of the night auditor at a 4-star hotel in Seminyak, Bali, Indonesia and what steps must be taken by the night auditor to increase the effectiveness of the night auditor at the hotel. Research methods: Sampling in this study used purposive sampling by taking samples that fit certain criteria, namely front office manager and night auditor. The data in this research was obtained through observation, documentation, and interview. The analysis technique in this study uses a qualitative descriptive analysis technique using the theory of Miles and Huberman in 1992 about interactive data analysis and analyzes using an effective theory approach using the effectiveness formula. Results and discussion: There is a decrease in the effectiveness of night auditor works at the hotel based on indicators of quantity, quality, and working time. These results can be seen from the summary of the result of interviews with all night auditors that each night auditor provides answers regarding the quantity, quality, and working time in serving as a night auditor so far as effective and ineffective. Therefore, the researcher concludes based on the results of the calculation of the effective formula that the results are worth 0.7, 0.9, and 0.85, which means it is smaller than 1, so it can be concluded that work effectiveness is not effective. Implication: The steps in increasing the effectiveness of the night auditor work are obtained from the results of interviews with the Front Office Manager which requires a good work ethic, a psychological environment, focus on work, working according to procedures, and understanding work procedures, and having time efficiency. Keywords: work effectiveness, night auditor, front office, hotel.